If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + -6 = 43 Reorder the terms: -6 + -7x = 43 Solving -6 + -7x = 43 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -7x = 43 + 6 Combine like terms: -6 + 6 = 0 0 + -7x = 43 + 6 -7x = 43 + 6 Combine like terms: 43 + 6 = 49 -7x = 49 Divide each side by '-7'. x = -7 Simplifying x = -7
| x^4=13 | | 9p=-27 | | x^2+y^2+8-10y+25=0 | | 2x-9=-9 | | x^42=13 | | -2(3b+3)+(7b-8)=0 | | -5k^2+11k+52=4k | | 6=-6y+3(y+8) | | x-3=10x+30 | | 12x+16=12x-84 | | -7(-15)= | | -12x^2+x=3-4x^2+9x | | (3,-10)= | | 6x-3(x-1)=2x | | -10+4x=-10 | | 2x*3x=2 | | 9+x=5 | | 4(4-n)=6n-4 | | -6=x+3 | | Y-8=-16 | | 2.7q-2.6-1.8q=0.1q-4.3 | | 3r-8=32 | | 2m^2-9m-18=0 | | x^2+5x+5x+18=9 | | H=2r-16 | | 10+x=4 | | 3d+9=6d-12 | | 12+2c+9c-6-11c= | | 12y+3=7 | | b^2-8b-58=0 | | -4n+3-7n= | | 15y-6=11 |